Ultrasensitive and Fast Bottom‐up Analysis of Femtogram Amounts of Complex Proteome Digests1. Issue 51 (31st October 2013) - Sun, Liangliang; Zhu, Guijie; Zhao, Yimeng; Yan, Xiaojing; Mou, Si; Dovichi, Norman J.
<x xml:space="preserve">Abstract</x> Femtogram proteomics: An ultrasensitive capillary zone electrophoresis–mass spectrometry system that is based on an improved nanospray interface has been developed. This system is used for the analysis of picogram to femtogram amounts of E. coli digests; for example, over 100 proteins were identified from 16 pg digests by tandem mass spectrometry. AMTs=accurate mass and time tags.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>